Heaping blame on shame: 'Weaponising stigma' for neoliberal times. Issue 4 (July 2018) - Scambler, Graham
The focus of this article is the 'weaponising' of stigma in the neoliberal era. The article starts with a brief characterisation of the sociological literature on stigma before moving to characterise post-1970s financial capitalism, focusing on relations of class and command. It then examines (a) the distinctions between enacted and felt stigma (involving norms of shame) and enacted and felt deviance (involving norms of blame), and (b) the novel neoliberal dialectic between these two sets of norms. This critical exposition provides a platform for a sociological rethink. A case is made that the significance of stigma and deviance as defined here can only be grasped sociologically in terms of the prime macro-mechanism of financial capitalism, the class/command dynamic, and the interaction of relations of stigma and deviance with other social relations, most notably those of (class-based) exploitation, deriving from the possession of capital, and (command or state-based) oppression, deriving from the possession of power. This case is constructed via a consideration of changing policies in relation to disability, drawing on UK data but with a wider reference. The final part of the article addresses modes of resistance to the roles of capital and power in dictating the neoliberal dialectic of shame and blame. It is argued that effective resistance depends on the formation of alliances across and between diverse 'movement activities'. Expanding on the author's work with David Kelleher, it is suggested that there exists a plethora of 'resistance activities', ranging from specific and/or local campaigns to transnational, class, feminist and ethnic insurrections. What this adds up to is a strategy of 'permanent reform'. It is argued that the effective execution of this strategy presupposes a structural shift away from neoliberal ideology, the narrative of austerity and post-1970s financial capitalism. The potential effectiveness of the strategy of permanent reform is appraised, again, with reference to disability policy and practice.